The Unusual Reddish-Bloom Appearance in a Freshwater Fishpond at Kingolwira National Fish Farming Center, Morogoro, Tanzania - N. Kimambo, Offoro; R. Gumbo, Jabulani; A.M Msagati, Titus; Chikoore, Hector (International Journal of Environment, 2020)
The study aimed to examines a case of what constituted the uncommonly reddish-bloom appearance in the fishponds during the dry season (September 2018) at Kingolwira National Fish Farming Center located in Morogoro, Tanzania. The study used a benchtop FlowCAM® to investigate species’ morphology. One-time assessment of physico-chemical characteristics during the event was performed from the reddish and non-reddish fishponds. Images were compared with the available literature, but also t-test statistics were performed to examine the difference between the fishponds. The results show that the fishponds were significantly (p<0.05) different from each other in terms of physico-chemical parameters except for water temperatures. Furthermore, Microcystis species dominated the non-reddish fishpond whereas Euglenophytes species were pervasive in the reddish fishpond. The two species have the potential to produce secondary metabolites (toxins) or to produce a hypoxia condition that is harmful to the fishery, aquatic ecology, and human. To confirm toxicity nature and dynamics further, future studies should consider extensive and regular diurnal and long-term monitoring.